Single stage single phase active power factor corrected Ĉuk Topology Based AC-DC Converter - Md. Ismail Hossain; Mohammad Jahangir Alam (Institute of Advanced Engineering and Science, 2014)
This paper focuses on the analysis of a power factor correction (PFC) converter using close loop Ĉuk topology. Regardless of the input line voltage and output load variations, input current drawn by the buck or buck-boost converter is always discontinuous. The Boost converter suffers from high voltage stresses across the power electronic devices. The input current in Ĉuk converter is comparable to boost converter’s input current. In this paper output voltage is controlled by inner current and outer voltage control loop along with power factor correction (PFC). It shows less input current THD, nearly unity power factor and better output voltage regulation of AC-DC converter under variable input voltage and output load. In this paper the relative performance between normal diode rectifier, open loop Ĉuk rectifier and close loop Ĉuk rectifier is presented. An algorithm for implementing close loop Ĉuk rectifier in digital domain is developed and simulated.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5574